2009
DOI: 10.1002/ange.200805145
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization Nanolithography: Combination of Bottom‐Up and Top‐Down Fabrication To Grow Arrays of Monodisperse Gold Nanoparticles Along Peptide Lines

Abstract: Von oben und von unten: Schneisen in selbstorganisierten Monoschichten (SAM) auf einem Goldsubstrat wurden mit Peptidlinien gefüllt. Eine Kombination von Top‐down‐ (Peptidnanolithographie) und Bottom‐up‐Verfahren (Biomineralisation) ermöglichte es, monodisperse Goldnanopartikel auf diesen Peptidlinien abzuscheiden (siehe Bild). Die Zahl an Nanopartikeln auf den Linien war durch die Breite des Peptidmusters bestimmt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…12,13 Additionally, top-down and bottom-up techniques can be employed together for improved resolution and spatial control. 14 Block copolymers (BCPs) offer high spatial resolution through their self-assembly into periodically ordered, microphase-separated nanoscale morphologies at equilibrium. 15,16 The ability to tune BCPs by their architecture, relative block volumes, and Flory−Huggins interaction parameter to form a variety of morphologies with length scales on the order of tens of nanometers makes them an ideal platform for templating thin films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12,13 Additionally, top-down and bottom-up techniques can be employed together for improved resolution and spatial control. 14 Block copolymers (BCPs) offer high spatial resolution through their self-assembly into periodically ordered, microphase-separated nanoscale morphologies at equilibrium. 15,16 The ability to tune BCPs by their architecture, relative block volumes, and Flory−Huggins interaction parameter to form a variety of morphologies with length scales on the order of tens of nanometers makes them an ideal platform for templating thin films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ligand interactions with nanoparticles (NPs) and NP/NP interactions are implicated in essentially all NP applications including bottom-up device fabrications, biosensing, cancer therapy, and catalysis . Collective oscillations of free electrons in plasmonic NPs under resonance excitations generate strong local electrical fields, which lead to surface-enhanced optical spectroscopic phenomena including surface-enhanced Raman spectroscopy (SERS).…”
Section: Introductionmentioning
confidence: 99%
“…A similar AgNP LSPR change has been observed with aromatic organothiol binding with AgNPs, 11 which was attributed to the organothiol conversion of surface silver atoms into insoluble RS-Ag salts accumulated on the AgNP. 1,19 Consequently, the dielectric constant of the medium surrounding the AgNP is increased, but the metal core size is reduced. Computational modeling showed that such a NP structural change induces red-shift of the AgNP LSPR peak and reduces AgNP LSPR peak absorbance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Examples include the intricate nano‐ and microcrystalline structures found in mollusk shells,1 coccoliths,2 and eggshells,3 which imbue the shells with important physical properties. Recent work has exploited biomolecules4, 5 and biomimetic processes6, 7 to fabricate new materials, but the scope for this would be greatly enhanced if the mechanism by which the biomolecules effect this control were better understood. Molecular simulation should be an ideal tool for identifying these mechanisms.…”
mentioning
confidence: 99%